TRANSLATIO AND COMPARATIVE LITTERATURE: THE TERROR OF EUROPEAN HUMANISM - Readings, Bill (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1991)
The interest of comparative literature as its divided relation to the function of translation. Critique of the terror of European humanism and insistence on the minoritarian reading of literature, on translation as an encounter with difference.